Developing novel fusion tags to facilitate protein production and structure determination - Maurer, Sigrun (2021)
Covalently fused protein tags can be a helpful tool in protein structure determination by X-ray crystallography and Cryo-electron microscopy. Carrier-driven crystallisation can aid protein structure determination, but the currently available selection of crystallisation tags is limited. Extant tags aim to increase solubility, provide additional crystal contacts, and can help in model building by molecular replacement. In addition, scaffold tags for electron microscopy (EM) techniques can help visualisation and structure determination, when target proteins would otherwise be of insufficient size for EM approaches.